Web-based processing of physiological noise in fMRI: addition of the PhysIO toolbox to CBRAIN - Valevicius, Darius; Beck, Natacha; Kasper, Lars; Boroday, Sergiy; Bayer, Johanna; Rioux, Pierre; Caron, Bryan; Adalat, Reza; Evans, Alan C.; Khalili-Mahani, Najmeh (Frontiers in Neuroinformatics, 2023)
Neuroimaging research requires sophisticated tools for analyzing complex data, but efficiently leveraging these tools can be a major challenge, especially on large datasets. CBRAIN is a web-based platform designed to simplify the use and accessibility of neuroimaging research tools for large-scale, collaborative studies. In this paper, we describe how CBRAIN's unique features and infrastructure were leveraged to integrate TAPAS PhysIO, an open-source MATLAB toolbox for physiological noise modeling in fMRI data. This case study highlights three key elements of CBRAIN's infrastructure that enable streamlined, multimodal tool integration: a user-friendly GUI, a Brain Imaging Data Structure (BIDS) data-entry schema, and convenient in-browser visualization of results. By incorporating PhysIO into CBRAIN, we achieved significant improvements in the speed, ease of use, and scalability of physiological preprocessing. Researchers now have access to a uniform and intuitive interface for analyzing data, which facilitates remote and collaborative evaluation of results. With these improvements, CBRAIN aims to become an essential open-science tool for 1 Addition of the PhysIO toolbox to CBRAIN integrative neuroimaging research, supporting FAIR principles and enabling efficient workflows for complex analysis pipelines.